INDONESIAN JUSTICE LEGAL POLITICS POST AMENDMENT OF 1945 CONSTITUTION - Aladin Sirait (Al-IHKAM: Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2020)
The essence of change in the field of justice after the amendment is a change in the system of judicial power at the constitutional and statutory levels. The creation of new supreme judicial institutions namely the Constitutional Court, in addition to the Supreme Court as the bearer and executor of the highest judicial powers in the presence of an independent Judicial Commission and cannot be separated from the powers of the judiciary. Legal politics that gave birth to the Constitutional Court Institution in its scope of duties and authority has played a large and important role in the goal of realizing justice. The Judicial Commission in its duties and authorities can substantially improve law enforcement in the environment and justice within the Supreme Court by proposing the appointment of a Chief Justice to the House of Representatives (DPR). The Supreme Court made progress with the issuance of Guidelines for the Implementation of Oversight within the Judiciary and the Joint Decree of the Chair of the Supreme Court and the Chair of the Judicial Commission on the Code of Ethics and the Code of Conduct for Judges. The Constitutional Court and Judicial Commission in its position as a high state institution with a strict division of tasks and authority has played a role in the creation of checks and balances mechanisms.